Advanced Practice Nursing: A Case Report of Pediatric Patients with Graft-versus-Host Disease - Kittithornruengchai, Sasiprapa; Punyoo, Jiraporn (Thai Journal of Nursing and Midwifery Practice, 2025)
Abstract: Hematopoietic stem cell transplantation (HSCT) is a treatment option for patients with cancer and other diseases related to abnormal hematopoiesis in the bone marrow. Although this treatment increases the chances of recovery from the disease, patients remain at risk of severe complications after HSCT, especially complication of graft-versus-host disease (GvHD) in pediatric patients. If pediatric patients have received untimely assessment and treatment, it could potentially lead to life-threatening consequences. This article presents an approach to caring for pediatric patients with GvHD, applying Orem’s nursing theory framework and the principles of empowerment to enhance the capacity of pediatric patients and their families in managing these disease conditions. Furthermore, the article highlights the role of Advanced Practice Nurses (APN) in providing holistic care to pediatric patients and their families, including assessment, planning, and psychosocial support to achieve positive health outcomes for pediatric patients, including improving the quality of life for pediatric patients and their families over the long term.